1994
DOI: 10.1136/jcp.47.9.864
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal hamartoma of liver in a man: comparison with cases in infants.

Abstract: A 53 year old man with a large mesenchymal hamartoma is reported. Only a few bile ducts could be found in the periphery of the lesion and no hepatocytes were identified within the lesion. As far as is known, this is the only adult male patient reported to date. On the basis of the reported findings of mesenchymal hamartoma in other adults, it is suggested that there could be changes in the morphology of this lesion with age: progressive loss of hepatocytes; degeneration of bile duct epithelium; and cystic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Since the appearance of tumor can vary from cystic to completely solid mass as well as a combination of both components, there is no consensus on which form of tumor is more common. Some authors have reported results which show higher frequency of cystic form in children [2], whereas others claim quite the opposite, that is they have found a higher frequency of solid mass tumor in pediatric age group [5]. The situation with adult patients is similar.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Since the appearance of tumor can vary from cystic to completely solid mass as well as a combination of both components, there is no consensus on which form of tumor is more common. Some authors have reported results which show higher frequency of cystic form in children [2], whereas others claim quite the opposite, that is they have found a higher frequency of solid mass tumor in pediatric age group [5]. The situation with adult patients is similar.…”
Section: Discussionmentioning
confidence: 77%
“…The situation with adult patients is similar. Chau et al [5] have reported higher frequency of cystic tumors, and Hernandez et al [9] have recorded higher frequency of cystic tumors in both adult and pediatric patients. It is believed that women are more prone to developing cystic tumors, and for men there is no tendency to any kind of tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported to occur in adults. 2,[5][6][7] The male: female ratio is 3 : 1, 8 and the tumor usually presents clinically as an abdominal swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Under 20 adult cases have been reported. [12][13][14][15][16][17][18][19][20][21][22][23][24] In all of these, there have been clear differences compared with the manifestations of the disease in childhood.…”
mentioning
confidence: 99%